Enhaching Primary Students’ Science Learning Outcome Utilizing Visual Multimedia - Nurmi Nurmi; Hadi Putra; Penti Nursida; Khoiro Mahbubah; Neni Hermita (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2018)
This study aims to improve 3rd grade students’ science learning outcomes bylearning to use visual multimedia. This research method uses classroom actionresearch. The subject of this research was the third grade students of secondsemester of elementary school which conducted 30 students. Based on theresults of research by using visual media, it have been found that theimprovement learning outcome, seen from the initial average score before theaction of 3rd grade class students from 65.5 to 83.83. The results of this studyindicate that with the use of visual media can improve student learningoutcomes.